Kemampuan Siswa Kelas VIII dalam Menyelesaikan Soal Cerita TIK pada Kurikulum Merdeka Berbasis Cinta di MTsN 7 Agam - Afwana; Zulfani Sesmiarni (Lembaga Yasin AlSys, 2026)
Students’ low ability to solve word problems in Information and Communication Technology (ICT) is evident in their difficulties in understanding information, determining solution strategies, and connecting Informatics concepts with contextual problems. This study aims to analyze the ability level of eighth-grade students at MTsN 7 Agam in solving ICT word problems within the Kurikulum Merdeka Berbasis Cinta. The study employed a quantitative approach using a descriptive method. The study population comprised 256 eighth-grade students, while a sample of 156 students was determined using the Slovin formula. Data were collected through questionnaires and documentation and were subsequently analyzed using descriptive statistics with the percentage technique. The results showed that students’ ability to solve ICT word problems was in the low category. The students’ main difficulties included understanding the content of the problems, identifying important information, determining solution steps, connecting Informatics concepts with the given problems, and obtaining correct answers. These findings confirm that students’ computational thinking and problem-solving abilities still need to be improved. This study provides practical implications for teachers to implement more contextual learning strategies, provide more practice with word problems, and optimize the implementation of the Kurikulum Merdeka Berbasis Cinta to improve computational thinking skills and the quality of ICT learning.